The Costs of Corruption and the Loss of Democratic Stability in Peru: Impact on Public Policy, Criminal Policy, and Transparency - Hurtado Niño De Guzmán, Edinson Wilber (2025)
The costs of corruption in Peru directly affect the development and progress of the Peruvian State. According to reports from the Office of the Comptroller General for the period 2021–2024, millions of soles have been lost in recent years due to acts of corruption, prompting the State to adopt public policy measures to reverse the situation. However, these efforts have not been reflected in economic indicators. The objective of this research is to analyze the cost of corruption and its impact on public policy, criminal policy, and transparency in our country. The study follows a qualitative and documentary design, based on an exhaustive systematic review of bibliographic sources and the compilation of definitions of the categories addressed.